Transformation of Esthetics in Postmodern Art - İLDEN, Serkan; MUTLU, Esma (Alinteri Sosyal Bilimler Dergisi, 2020)
As an outcome of information or technology era since 1960s to date, post-modernism is considered as a process, in which extraordinary advancements and changes occurred and different discourses emerged in the fields such as painting, graphic, sculpture, architecture, philosophy, economics, and sociology involving the social life and culture. Postmodernism caused the emergence of new artistic discourses as a result of rapid change and development of artistic events in the current era, it transformed into different identities other than modern art and brought new concepts and perspectives to the art life. These concepts and perspectives are in opposition to modernism and they are very tough. Considering that the modern art’s elements such as mission, uniqueness, beauty, and proportion would limit the area of art, postmodern artists place the esthetic components into a populist structure in harmony with today’s living conditions. In the present study, the changes in postmodernist art after modernism will be discussed, postmodern art esthetic will be explained, and the transformation of artistic values within the frame of Pop-art and Conceptual Art will be examined.
Keywords: postmodern art; H; Social Sciences; postmodern culture; esthetic; social life; sculpture